Grape pomace as a source of phenolic compounds and diverse bioactive properties - Peixoto, Carla M. (2018)
The bio-residues resulting from the wine industry (grape pomace made up of skins, seeds and stems) are often undervalued but constitute a potential source of bioactive phenolic compounds that can be applied in several industries. In this context, the aim of the present study was to evaluate the phenolic profile of Vitis vinifera L. grape pomace (skins, seeds and their mixture), and correlate them with its antioxidant, cytotoxic and antibacterial activities. The seeds showed the highest amount of phenolic compounds and also the highest antioxidant, cytotoxic and antibacterial activities. The skins revealed the highest levels of anthocyanins and pcoumaric acid hexoside. Strong correlations were observed between the presence of phenolic compounds and all the bioactivities studied. These by-products are good sources of phenolic compounds with high antioxidant and antibacterial activity, and also presenting a moderate cytotoxicity activity. These added-value by-products have great applicability in food, pharmaceutical and cosmetic industries.